2019
DOI: 10.3390/metabo9050090
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Preterm Birth: Potential for a Metabolomics Biomarker Panel

Abstract: The aim of this preliminary study was to investigate the potential of maternal serum to provide metabolomic biomarker candidates for the prediction of spontaneous preterm birth (SPTB) in asymptomatic pregnant women at 15 and/or 20 weeks’ gestation. Metabolomics LC-MS datasets from serum samples at 15- and 20-weeks’ gestation from a cohort of approximately 50 cases (GA < 37 weeks) and 55 controls (GA > 41weeks) were analysed for candidate biomarkers predictive of SPTB. Lists of the top ranked candidate bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 46 publications
2
16
0
Order By: Relevance
“…In conclusion, this study reports reduced glycerophospholipids and sphingolipids at 20 weeks' gestation, prior to the onset of sPTB in women in the Cork SCOPE study. Our findings confirm and extend findings by Considine et al (2019), suggesting convergent metabolomic and lipidomic pathways in the same cohort of women (Considine et al 2019), which may serve as potential therapeutic targets or putative markers for the prediction of sPTB. Further research is needed to validate these findings in independent pregnancy cohorts.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In conclusion, this study reports reduced glycerophospholipids and sphingolipids at 20 weeks' gestation, prior to the onset of sPTB in women in the Cork SCOPE study. Our findings confirm and extend findings by Considine et al (2019), suggesting convergent metabolomic and lipidomic pathways in the same cohort of women (Considine et al 2019), which may serve as potential therapeutic targets or putative markers for the prediction of sPTB. Further research is needed to validate these findings in independent pregnancy cohorts.…”
Section: Discussionsupporting
confidence: 87%
“…2). In support of our observations in sPTB in SCOPE Cork, a recent metabolomic profiling study in the same cohort of women implicated bile acids, prostaglandins and Vitamin D as differentially expressed at 15 and 20 weeks' gestation (Considine et al 2019). This independent study which was performed at the University of Manchester, profiled metabolites using alternative extraction protocols (Dunn et al 2011) and LC-MS/MS analyses.…”
Section: Discussionsupporting
confidence: 81%
“…Similarly, a study reported that a panel of four mass spectrometry-derived metabolites could predict spontaneous PTB with a partial AUC (i.e. an alternative to AUC, whereby only the regions of ROC space where data are observed are included) of 12.6 in 105 women [ 27 ]. These studies did not compare their models to the existing risk factors or undertake external validation.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a study reported that a panel of four mass-spectrometry derived metabolites could predict spontaneous PTB with a partial AUC (i.e. an alternative to AUC, whereby only the regions of ROC space where data are observed are included) of 12.6 in 105 women 27 . These studies did not compare their models to existing risk factors or undertake external validation.…”
Section: Introductionmentioning
confidence: 99%